Multidirectional Plyometric Training: Very Efficient Way to Improve Vertical Jump Performance, Change of Direction Performance and Dynamic Postural Control in Young Soccer Players - Jlid, Mohamed C.; Racil, Ghazi; Coquart, Jeremy; Paillard, Thierry; Bisciotti, Gian Nicola; Chamari, Karim (Frontiers in Physiology, 2019)
ABSTRACT The aim of the study was to assess the effects of multidirectional plyometric training (MPT) on vertical jump height, change of direction performance (CODP) and dynamic postural control (DPC) in young soccer players. Twenty-eight young male soccer players were randomly assigned to an experimental group (EG, n=14; age: 11.8±0.4 years,) and a control group (CG, n=14; age: 11.6±0.5 years).The EG introduced 8-week MPT, two days per week into their in-season training, while CG continued training without change. Measurements of vertical jump height, CODP and DPC were completed at the beginning and end of the 8-week MPT. A significant group × time interaction was observed for Squat-Jump (p<0.05), for Counter-Movement Jump (p<0.05) and for CODP test (p<0.05). In addition, a significant group × time interaction was observed for DPC in seven axes for the dominant- (anterior, lateral, postero-lateral, posterior, postero-medial, medial and antero-medial; p < 0.05 for all) and in seven axes for the non-dominant- (anterior, antero-lateral, lateral, posterior, postero-medial, medial and antero-medial; p < 0.05 for all) legs. The rest of the axes of both legs did not show any significant group × time interaction (p>0.05). In conclusion, incorporating MPT into the in-season regimen of young male soccer players improved performance of various indices related to soccer activity (i.e., vertical jump height, CODP and DPC). MPT has the potential to be appealing to coaches, as it requires little time while yielding valuable results in the physical preparation of young soccer players.